2016
DOI: 10.1039/c6cy00836d
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum phosphide as a novel and stable catalyst for dry reforming of methane

Abstract: A novel MoP catalyst exhibited high coking and oxidation resistance for dry reforming of CH4with CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…19 Strong CO adsorption on MoP (001) was also reported by Liu et al, 20 in their theoretical study. In another recent theoretical study, the CO saturation coverage on Mo-terminated MoP (001) was reported to be 1 ML with CO desorption occurring above 500 K. 21 Also experimental investigations, conducted by Yao et al, 22 found MoP to be active toward CO 2 reforming of methane with better activity and stability compared to Ni/ Mo 2 C. 22 Additionally, strong oxygen to phosphorus interaction on nickel phosphide Ni 2 P (001) catalyst has been shown to facilitate the direct water gas shift reaction. 11 Another interesting feature of TMPs is attributed to its hydrotreating abilities which favor easier H 2 dissociation on catalyst surface.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…19 Strong CO adsorption on MoP (001) was also reported by Liu et al, 20 in their theoretical study. In another recent theoretical study, the CO saturation coverage on Mo-terminated MoP (001) was reported to be 1 ML with CO desorption occurring above 500 K. 21 Also experimental investigations, conducted by Yao et al, 22 found MoP to be active toward CO 2 reforming of methane with better activity and stability compared to Ni/ Mo 2 C. 22 Additionally, strong oxygen to phosphorus interaction on nickel phosphide Ni 2 P (001) catalyst has been shown to facilitate the direct water gas shift reaction. 11 Another interesting feature of TMPs is attributed to its hydrotreating abilities which favor easier H 2 dissociation on catalyst surface.…”
Section: Introductionmentioning
confidence: 96%
“…In another recent theoretical study, the CO saturation coverage on Mo-terminated MoP (001) was reported to be 1 ML with CO desorption occurring above 500 K . Also experimental investigations, conducted by Yao et al, found MoP to be active toward CO 2 reforming of methane with better activity and stability compared to Ni/Mo 2 C . Additionally, strong oxygen to phosphorus interaction on nickel phosphide Ni 2 P (001) catalyst has been shown to facilitate the direct water gas shift reaction .…”
Section: Introductionmentioning
confidence: 97%
“…For examples, MoP catalyst prepared by adding citric acid contained high surface area and delivered higher activity for hydrodeoxygenation of 4-methylphenol compared with MoP without citric acid added. [19] Yao et al [20] reported that MoP exhibited high activity and stability for dry reforming of CH 4 with CO 2 . However, so far, there was no literature for MoP-based catalysts applied in CO methanation reaction.…”
Section: Other Informationmentioning
confidence: 99%
“…Unsupported molybdenum carbides are generally covered by carbon, and the obtained surface areas of around 30 m 2 /g [ 9 ] are not optimal for catalysis. Alternatively, some organic precursors have been employed; however, the active phase generally remains covered with carbon from the precursor [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%